Enhanced cancer immunotherapy via synergistic action of NO-Donor nanoparticles (NanoARG) and PD-1 antibody - Mei Ting; Xin Zhang; Xiaolu Hou; Yukio Nagasaki (Science and Technology of Advanced Materials, 2025)
This study explores the synergistic potential of PEG-b-P(L-Arg)-based polyion complex micelles (NanoARGs) combined with an immune checkpoint inhibitor (PD-1 antibody) for cancer immunotherapy. Comprehensive experiments, including micelle preparation, in vivo anti-tumor activity evaluation, nitric oxide (NO) quantification, and immunofluorescence analysis, revealed significant insights. NanoARGs exhibited a biphasic effect on tumor growth: high doses inhibited tumor growth through NO generated from liberated Arg, whereas low doses promoted tumor progression. The combination treatment demonstrated significant synergistic anti-tumor activity without notable adverse effects, and treated mice tolerated the regimen well. This approach elevated NO levels in serum and tumor tissues, enhanced immune cell infiltration into tumor tissues, and facilitated the polarization of tumor-associated macrophages to the M1 phenotype. PD-1 antibody further amplified these effects by blocking PD-1/PD-L1 interactions and reactivating T cells. These results underscore the therapeutic potential of this novel approach, providing a foundation for optimizing tumor immunotherapy strategies and advancing clinical applications. Future research will focus on elucidating the mechanisms of action and expanding the scope of this promising treatment.